IUTAM Symposium on Intelligent Multibody Systems - Dynamics, Control, Simulation - Zahariev, Evtim; Cuadrado, Javier; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume, which brings together research presented at the IUTAM Symposium Intelligent Multibody Systems - Dynamics, Control, Simulation, held at Sozopol, Bulgaria, September 11-15, 2017, focuses on preliminary virtual simulation of the dynamics of motion, and analysis of loading of the devices and of their behaviour caused by the working conditions and natural phenomena. This requires up-to-date methods for dynamics analysis and simulation, novel methods for numerical solution of ODE and DAE, real-time simulation, passive, semi-passive and active control algorithms. Applied examples are mechatronic (intelligent) multibody systems, autonomous vehicles, space structures, structures exposed to external and seismic excitations, large flexible structures and wind generators, robots and bio-robots. The book covers the following subjects: -Novel methods in multibody system dynamics; -Real-time dynamics; -Dynamic models of passive and active mechatronic devices; -Vehicle dynamics and control; -Structural dynamics; -Deflection and vibration suppression; -Numerical integration of ODE and DAE for large scale and stiff multibody systems; -Model reduction of large-scale flexible systems. The book will be of interest for scientists and academicians, PhD students and engineers at universities and scientific institutes.
Preface -- Scientific Committee -- Organizing Committee -- Reviewers -- List of Sponsors -- Selected Challenges in Realistic Multibody Modeling of Machines and Vehicles, by Jorge Ambrósio -- Musculo-skeletal modeling and analysis for low-cost active orthosis customization and SCI patient adaptation, by Javier Cuadrado, Urbano Lugris, Francisco Mouzo and Florian Michaud -- Comparison and Analysis of Multibody Dynamics Formalisms for Solving Optimal Control Problem, by Quentin Docquier, Olivier Bruls and Paul Fisette -- A Recursive Driving Constraint Approach for Inverse Dynamics Modeling of Flexible Multibody Systems, by Saeed Ebrahimi and Arman Mardani -- Probabilistic Solutions of the Stretched Beam Systems Formulated by Finite Difference Scheme and Excited by Gaussian White Noise, by Guo-Kang Er, Vai Pan Iu, Kun Wang and Hai-En Du -- O(n) Algorithm for Elastic Link/Joint Robots with End-Effector Contact, by Hubert Gattringer, Andreas Müller, Florian Pucher, and Alexander Reiter -- Developing a3-D, lumped-mass model to present behaviour of large deformation surface based continuum robots, by Hossein Habibi, Rongjie Kang, Ian D. Walker, Isuru S. Godage and David T. Branson -- Research and Development of Methods and Tools for Rapid Digital Simulation and Design of Personalized Orthoses, by Iliya Savov, Georgi Todorov, Yavor Sofronov and Konstantin Kamberov -- Dynamic Modeling of a Sheep Hair Shearing Device using RecurDyn and its Verification, by Sasanka Sekhar Sinha.and Subir Kumar Saha -- Seismic response of soil-structure systems via BIEM and FEM in absolute coordinates, by Evtim Zahariev and Petia Dineva -- Author Index.
Keywords: Mechanics, Applied; Mechatronics; Mathematics -- Data processing; Mathematical physics; Engineering Mechanics; Mechatronics; Computational Science and Engineering; Theoretical, Mathematical and Computational Physics